Research trends and topics on sepsis immunosuppression: a bibliometric and visual analysis of global research from 2004 to 2024 - Ji Yin; Yantong Wan; Guangqin Chen; Nanhong Li; Fei Liu; Haihua Luo; Haihua Luo; Haihua Luo; Haihua Luo; Haihua Luo; Yijing Li; Shan Li; et al. (Frontiers in Medicine)
BackgroundSepsis, a condition characterized by critical organ impairment resulting from dysregulated response to infection, remains a leading cause of mortality globally. Immunosuppression significantly dictates the clinical trajectory and ultimate prognosis in sepsis. Research on sepsis-related immunosuppression has gained substantial attention in recent years. However, a comprehensive and objective analysis of the current state of research remains scarce. This study employs bibliometric techniques and knowledge mapping to provide a visual analysis of trends and developments in sepsis immunosuppression, offering a systematic overview for researchers in the field.ObjectivesThis study aims to: (1) Quantitatively characterize global publication trends, key contributors (countries/institutions/journals/authors), and collaborative networks in sepsis immunosuppression research (2004–2024); (2) Identify current hotspots and future directions in this field.Materials and methodsArticles and reviews related to sepsis immunosuppression were sourced from the Web of Science Core Collection via subject-specific searches. Bibliometric analyses were executed using Excel 365, CiteSpace, VOSviewer, and Bibliometrix (R-Studio’s R-Tool).ResultsFrom January 1, 2004, to March 22, 2024, 3,082 articles on sepsis immunosuppression authored by 16,545 individuals across 116 institutions from 30 countries were identified. Collaborative network analysis highlights the United States as the leading contributor, with key institutions including the University of Florida and Washington University. Strong international collaboration is evident, particularly between the United States and China, as well as the United States and Germany. Frontiers in Immunology emerged as the most prolific journal, while Journal of Immunology garnered the highest co-citation frequency. Guillaume Monneret has published the greatest number of relevant articles, while Richard S. Hotchkiss is the most frequently co-cited author. The research predominantly focuses on immunology, molecular biology, and clinical treatments. Keyword analysis suggests that immune cells, cell death, and personalized clinical treatments are emerging research hotspots in the field.ConclusionThis bibliometric analysis maps evolving trends and forecasts emerging hotspots in sepsis immunosuppression research, providing direction for future studies.